Educating the nation about Union – Whose heritage? (Yesterday & Today Journal for History Education in South Africa and abroad, 2010)
On the 31st of May 2010, South Africa, as a geopolitical creation, had beenin existence for a century; a momentous occasion for the country. However, the day passed with little acknowledgement of this event. The question that needs to be asked is why? Surely, the centenary of the geopolitical creation of a country should be commemorated as it is a time to reflect where the country has come from? Thus the focus of this article is the lack of commemoration of Union in 2010 and History Education. The centenary of Union was not commemorated and this phenomenon needs to be unpacked and understood. The Union forms part of the heritage of all South Africans but this it not deemed so by the state. In terms of education, the history of Union will be forgotten as it is not studied and the importance of the creation of South Africa as a geopolitical unit will fall by the waste side. Therefore, the purpose of this article is to unpack the notion of heritage and Union, its exclusion from the National Curriculum Statement (NCS), the non commemoration of its centenary, the significance of Union to society and its recent inclusion into the new Curriculum and Assessment Policy (CAPS) document.
Keywords: Union of 1910; Heritage; Commemoration; History Education; South Africa; Nation building